IMPLEMENTASI SPORT MASSAGE DI CAR FREE DAY CIANJUR - Aryani, Mela; Kastrena, Ervan; Afriyuandi, Asep Ramdhan; Rahadian, Adi; Pratama, Andi Kurniawan; Rochman, Taupik; Yudho, Firdaus Hendry Probowo; Amalia, Eneng Fitri; Taufik, Muhamad Syamsul; Lakana, Goesti Sabda; Mulyadi, M. Sandi; Augusti, Andini Suci; Sidik, Fahmi Maulana; Marchan, Dandi; Sungkawa, M. Guntur Gaos (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Cianjur is one of the district capitals in West Java with a dense population, but it is difficult for people to find qualified masseurs, especially sports massage. Massage courses are compulsory courses that must be taken by PJKR Element students to fulfill their credits. Massage courses are unique courses because students must understand theory and practice. Therefore, we as lecturers and students carry out community service by holding free sports massages in places that are often visited by the community, namely the Cianjur city car free day, which aims to ensure that people can feel the benefits of these activities, including the body becoming fresher, not sore, feeling more relaxed and so on so that people get benefits from these activities. This PKM activity was carried out during two meetings on February 11-18, 2024 with a total of 327 massage objects from various educational backgrounds and professions.The community felt happy and satisfied and hoped that similar activities could be carried out every week.